2020
DOI: 10.1186/s12885-020-07244-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact on quality of life 3 years after diagnosis of prostate cancer patients below 75 at diagnosis: an observational case-control study

Abstract: Background: Prostate cancer patients are known to suffer from poor sexual and urinary long-term side-effects following treatment, potentially impacting quality of life. The purpose of our study was to compare health-related quality of life at 3 years between prostate cancer patients and healthy controls according to key lifestyle characteristics. Secondary objectives were to compare urological dysfunction, sexual function, anxiety and depression. Methods: Multicentric, case-control, observational prospective, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Furthermore, prostate cancer affected soldiers' physical, sexual, mental, social and financial wellbeing. These findings are parallel with existing studies [15,16]. Evidence shows that depression is common among persons living with prostate cancer [17].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, prostate cancer affected soldiers' physical, sexual, mental, social and financial wellbeing. These findings are parallel with existing studies [15,16]. Evidence shows that depression is common among persons living with prostate cancer [17].…”
Section: Discussionsupporting
confidence: 90%
“…PCa, as one of the most common malignant tumors, has the second highest incidence and the sixth highest mortality worldwide ( 1 , 2 ) Although the incidence of PCa in China is far less likely to that in Western countries, its growth in the developing country is much faster ( 3 , 4 ). As China gradually enters the aging society, PCa will become the main tumor “killer” that endangers the health of elderly men; therefore, the clinical diagnosis and treatment of PCa and its basic study have entered an urgent stage ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) is one of the most common malignancies among men in Western countries and the second most common malignancies in the United States ( 1 , 2 ). It is reported that 191,930 new cases and 33,330 new deaths of PCa were found among all men in the United States in 2020 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nurses instructed the patients to choose suitable stoma care supplies and carefully explained and demonstrated the replacement of urostomy pouches and precautions. They also carried out clinical health education, with diet and discharge guidance to the patients [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%